Study of Transient Heat Transfer of Melt in Ellipsoidal Lower Head - LIU Peng1, 2, 3, ZHOU Tao1, 2, 3, LIU Xiaofang1, 2, 3, ZHANG Haolei1, 2, 3, BAI Zongyan1, 2, 3, DUN Shilei1, 2, 3, MAO Shang4 (Yuanzineng kexue jishu)
The in-vessel melt retention (IVR) technology, as one of the typical technologies to cope with severe accidents in third-generation nuclear power, is widely used in pressurized water reactor (PWR) nuclear power plants. Based on the study of VVER-1000 under severe accidents, melt was retained in the lower head of the ellipsoidal pressure vessel, a transient heat transfer model for melt retention in the ellipsoidal lower head under severe accidents in reactors was developed by using Python language, the transient heat transfer process of the molten pool in the ellipsoidal lower head was computed, the transient trends of the main stream temperature, the wall heat flux, the thickness of oxidic crust and the thermal resistance distribution of the molten pool in the ellipsoidal lower head were analyzed. The results show that the main stream temperature of the oxidic pool and the metal layer shows an exponential decay law, similar to the trend of the volume heat release rate inside the molten pool. After 400 ks of serious accidents, the decreasing trend of the decay heat power of the molten pool, the main stream temperature and the wall heat flux gradually become flat, and it can be initially considered that the ellipsoidal molten pool will be in a long-term cooling state, and the thermal parameters inside the molten pool will not change substantially, and the molten pool will be in a relatively stable state. The pressure vessel wall heat flux of each place decays over time, and the heat flux attenuation trend of the metal layer in contact with the pressure vessel wall is the most intense. The heat flux at the contact part between the pressure vessel wall and the metal layer reaches its maximum value, while the heat flux at the bottom of the oxidation tank wall is the smallest, the metal layer has a thermal focusing effect, the place is also the most vulnerable to failure of the pressure vessel part. The closer to the upper part of the oxidic pool, the faster the growth of the oxidic crust thickness, but the growth rate of the oxidic crust thickness slows down with time, the thickness of the oxidic crust decreases with the increase of the axial height of the oxidic pool. Oxidic crust also occupies a major part of the thermal resistance of the molten pool, the largest thermal resistance of the oxidic crust generates at bottom of the molten pool, from the nuclear safety point of view, the appearance of the oxidic crust resistance plays the role of thermal insulation, the integrity and safety of the pressure vessel is protected to a certain extent.